"He did that because I was Black": Black College Students Perceive Municipal Police, Not Campus Police, as Discriminating. Issue 1 (2nd January 2020) - Allen, Andrea; Jacques, Scott
ABSTRACT: This article examines qualitative data obtained from 66 Black college students about perceptions of their interactions with municipal police (MP) and campus police (CP). Participants described MP and CP as acting severely, but only attributed racial bias to MP. These findings are explored with respect to theories of procedural justice and legitimacy. They help to explain why participants viewed MP's actions as racially biased, though it is less clear why CP's actions were not perceived as such.